Wychowanie ku dobru – w perspektywie Tischnerowskiej koncepcji człowieka agatologicznego - Dariusz Adamczyk (Studia Koszalińsko-Kołobrzeskie, 2015)
The article concerns issues of education in agathological prospect. Base of this education determines philosophical reflection on a human as a being, which aim is entire development towards the fullness of humanity. This reflection is taken by Joseph Tischner. His concept of agathological human is concentrating on realisation and concentration of axiological „I”, as a result of relations human to quality. Dialogical meeting between pupil and tutor is significant in this prospect in the process of education, which determines chance on experiencing value and moving towards the goodness. Main tutor responsibilities are necessity of evidencing about goodness and inspiring the pupil to searching creative ways in his life.